Flat and rounded contacts - modelling the effect of a moment with application to fretting fatigue tests - Truelove, J; Hills, D; Blades, L (SAGE Publications, 2022)
The problem of elastic indentation by a punch having the form of a flat front face but with edge rounding, and subject to both a normal load and moment, indenting an elastically similar half-plane is considered. Contact pressure in the neighbourhood of the edges shows a local peak, and the object of the paper is to show how different combinations of normal load and moment can give rise to the same near edge behaviour and peak pressure. The result found is very simple, and of direct practical application in fretting fatigue studies, both analytical and experimental.